Lessons from the Sub-Prime Crisis - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2007)
We show that there is significant variation in performance across hedge funds during the subprime crisis. Hedge funds that (i) invested in Asia, (ii) had equity exposure, (iii) adopted directional strategies, or (iv) allowed for frequent redemptions, underperformed other funds. Moreover, leveraged funds did not fare significantly worse than their non-leveraged counterparts. Our results suggest that credit market illiquidity was not directly responsible for the bloodshed amongst hedge funds. Rather, funds were hurt by an increase in global risk aversion and by fire sales conducted in anticipation of redemptions.